Position statement: a clinical approach to the management of adult non‐neurogenic overactive bladder. Issue 1 (15th January 2018) - Chung, Eric; Lee, Dominic; Gani, Johan; Gillman, Michael; Maher, Christopher; Brennan, Janelle; Johns Putra, Lydia; Ahmad, Laura; Chan, Lewis LW
Summary: Introduction: Overactive bladder (OAB) is a highly prevalent medical condition that has an adverse impact on various health‐related quality‐of‐life domains, including a significant psychosocial and financial burden. This position statement, formulated by members of the Urological Society of Australia and New Zealand and the UroGynaecological Society of Australasia, summarises the current recommendations for clinical diagnosis and treatment strategies in patients with non‐neurogenic OAB, and guides clinicians in the decision‐making process for managing the condition using evidence‐based medicine. Main recommendations: Diagnosis and initial management should be based on thorough clinical history, examination and basic investigations to exclude underlying treatable causes such as urinary tract infection and urological malignancy. Initial treatment strategies for OAB involve conservative management with behavioural modification and bladder retraining. Second‐line management involves medical therapy using anticholinergic or β3 agonist drugs provided there is adequate assessment of bladder emptying. If medical therapy is unsuccessful, further investigations with urodynamic studies and cystourethroscopy are recommended to guide further treatment. Intravesical botulinum toxin and sacral neuromodulation should be considered in medical refractory OAB. Changes in management as a result of this statement: OAB is a constellation of urinary symptoms and is a chronic condition with a low likelihood of cure; managing patient expectations is essential because OAB is challenging to treat. At present, the exact pathogenesis of OAB remains unclear and it is likely that there are multiple factors involved in this disease complex. Current medical treatment remains far from ideal, although minimally invasive surgery can be effective. Further research into the pathophysiology of this common condition will hopefully guide future developments in disease management.